2007
DOI: 10.1007/s12010-007-0011-x
|View full text |Cite
|
Sign up to set email alerts
|

Production of Raw Starch-Saccharifying Thermostable and Neutral Glucoamylase by the Thermophilic Mold Thermomucor indicae-seudaticae in Submerged Fermentation

Abstract: The effect of temperature on the performance of an anaerobic sequencing biofilm batch reactor (ASBBR) with liquid-phase recirculation was assessed. Assays were performed using a recirculation velocity of 0.20 cm/s, 8-h cycles, and an average treated synthetic wastewater volume of 2 L/cycle with a concentration of 500 mg of Chemical Oxygen Demand (COD)/L. Operation temperatures were 15, 20, 25, 30, and 35 degrees C. At 25, 30, and 35 degrees C, organic matter removal efficiencies for filtered samples ranged fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 27 publications
2
13
0
Order By: Relevance
“…Studies of submerged PYT production using S. thermophile in cane molasses medium showed that the productivity obtained in the 10-L working volume fermenter (5.2 IU/mL/day) was improved by a factor of 2.2 times from shake flask (2.5 IU/mL/day) experiments and having optimum activity at pH 5.5 and 45 °C (Singh and Satyanarayana 2008). Similar trend of increased productivity by 1.5 times for glucoamylase production was observed by Kumar et al (2007). …”
Section: Discussionsupporting
confidence: 87%
“…Studies of submerged PYT production using S. thermophile in cane molasses medium showed that the productivity obtained in the 10-L working volume fermenter (5.2 IU/mL/day) was improved by a factor of 2.2 times from shake flask (2.5 IU/mL/day) experiments and having optimum activity at pH 5.5 and 45 °C (Singh and Satyanarayana 2008). Similar trend of increased productivity by 1.5 times for glucoamylase production was observed by Kumar et al (2007). …”
Section: Discussionsupporting
confidence: 87%
“…Spores were counted under compound microscope using haemocytometer, and their viability was checked by plating 0.1 ml of a suitable dilution on Emerson YpSs agar plates incubated at 40°C for 24 h. Glucoamylase production was carried out by inoculating 250-ml Erlenmeyer flasks containing 50 ml sucrose-yeast extract medium with ∼5×10 6 sporangiospores and incubating at 40°C in an incubator shaker at 250 rpm [18]. After 48 h, the fermented broth was filtered through Whatman no.…”
Section: Glucoamylase Productionmentioning
confidence: 99%
“…Industrial enzymatic hydrolysis is influenced by a number of factors amongst which are environmental conditions of pH, temperature and presence of metal ion (Riaz et al, 2007). Amylases have been reported to be produced by a number of fungi, including Aspergillus, Rhizopus, Fusarium, Candida, Penicillium, Thermomucor, basidiomycete Fomitopsis and Thermomyces (Balkan et al, 2005, Kumar et al, 2007, Kunamneni et al, 2004, Mohamed et al, 2007, Yoon et al, 2006. Majority of the studies on fungal amylases are based on mesophiles, rarely on facultative thermophiles (Maheswari et al, 2000).…”
Section: Introductionmentioning
confidence: 99%